Sosialisasi Perawatan Luka pada Masa New Normal di Lembaga Pembinaan Khusus Anak Kelas I Medan - Rani Kawati Damanik; Laura Mariati Siregar; Agnes Silvina Marbun (PT.Mantaya Idea Batara, 2021)
Implementation of socialization can increase the knowledge of respondents. A person who initially does not know becomes an expert at doing something. The effectiveness of the implementation of a socialization can be measured from three things, namely input, conversion, and output. This community service activity can increase knowledge about wound care. We often encounter wounds in the community, thus demanding our knowledge in order to be able to treat wounds independently. Implementation of community service activities by conducting pre-test,socialization and post-test. The results showed that the level of knowledge of respondents about wound care carried out at the Class I Medan Special Children's Development Institute found that the increase in respondents' knowledge was very significant, namely before being given socialization, 11 people (73%), less knowledge were obtained, while after being given socialization increased so that the level of knowledge the majority is sufficient as much as 10 people (67%).